Geographer - Starting Again as a Specialist or Generalist? - Wong, Poh Poh (Advances in Social Sciences Research Journal, 2023)
A geographer states his personal insights on becoming a specialist or generalist with application for the budding scientist. Starting with the hindsight on planning one’s retirement plan the insights are on assessing critically your education, reading outside your areas, be prepared to work outside your comfort zone, becoming a good generalist when the occasion arises, and organizing your knowledge. At the end, one can see more opportunities to work as a specialist or generalist.